2010
DOI: 10.5565/rev/elcvia.361
|View full text |Cite
|
Sign up to set email alerts
|

Color Image Segmentation using Fast Fuzzy C-Means Algorithm

Abstract: This paper proposes modified FCM (Fuzzy C-Means) approach to colour image segmentation using JND (Just Noticeable Difference) histogram. Histogram of the given colour image is computed using JND colour model. This samples the colour space so that just enough number of histogram bins are obtained without compromising the visual image content. The number of histogram bins are further reduced using agglomeration. This agglomerated histogram yields the estimation of number of clusters, cluster seeds and the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the case, where only the mouth area is focused to obtain HR, it can impact the error rate when a person is talking or laughing as teeth do not provide a pulse signal to obtain HR. To cater to this problem, researchers [100] introduced neural networks for skin classification [163] to determine skin colour from the face image. This ROI (skin pixel) was labelled and tracked using a mean-shift tracker, which iteratively shifts points of data to the average of points of data nearby [108].…”
Section: Literature Review Findings: Previous Work With Its Limitationsmentioning
confidence: 99%
“…In the case, where only the mouth area is focused to obtain HR, it can impact the error rate when a person is talking or laughing as teeth do not provide a pulse signal to obtain HR. To cater to this problem, researchers [100] introduced neural networks for skin classification [163] to determine skin colour from the face image. This ROI (skin pixel) was labelled and tracked using a mean-shift tracker, which iteratively shifts points of data to the average of points of data nearby [108].…”
Section: Literature Review Findings: Previous Work With Its Limitationsmentioning
confidence: 99%
“…For accurate segmentation of a region in the brain, it is necessary to strip the skull part from the MR images [28]. After comparing the performance of five popular segmentation techniques namely Region-growing [29], Region splitting & Merging [30], K -Means algorithm [31], Histogram-based algorithm [32], and Fuzzy C Means [33] for 50 MRI images, it is found that the Histogram Based Thresholding technique gives the highest accuracy among all these algorithms [34]. Hence, for skull stripping, we have used the Histogram Based Thresholding technique.…”
Section: Preprocessingmentioning
confidence: 99%
“…Bhoyar and Kakde [34] proposed modified FCM (Fuzzy C-Means) approach to color image segmentation using JND (Just Noticeable Difference) histogram. The approach is compared with the (fuzzy c-means) FCM for segmentation, which is faster than FCM.…”
Section: Literature Studymentioning
confidence: 99%